Cochrane Database of Systematic Reviews 2015
DOI: 10.1002/14651858.cd010834.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Mepolizumab versus placebo for asthma

Abstract: It is not possible to draw firm conclusions from this review with respect to the role of mepolizumab in patients with asthma. Our confidence in the results of this review are limited by the fact that the intravenous route is not currently licensed for mepolizumab, and the evidence for the currently licenced subcutaneous route is limited to a single study in participants with severe eosinophilic asthma.The currently available studies provide evidence that mepolizumab can lead to an improvement in health-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 125 publications
1
37
0
1
Order By: Relevance
“…115 A Cochrane review was published in 2015. 116 The literature search was performed in 2013 and updated in 2014. Eight studies on 1,707 individuals were selected.…”
Section: Mepolizumabmentioning
confidence: 99%
“…115 A Cochrane review was published in 2015. 116 The literature search was performed in 2013 and updated in 2014. Eight studies on 1,707 individuals were selected.…”
Section: Mepolizumabmentioning
confidence: 99%
“…Most of these results were expected [26,27], but a global meta-analysis was lacking. Here, we selected significant studies and aggregated the results.…”
Section: Probability Of the Best Increase In Fevmentioning
confidence: 99%
“…However, since varied baseline of patients among studies, it is not possible to draw a firm conclusion. Different from previous systematic reviews that only included studies of on mepolizumab [38, 39], we included trials about mepolizumab and other two anti-interleukin-5 antibodies-reslizumab and benralizumab. Additionally, the results should be interpreted with caution due to with the relatively small sample sizes and small number of included trials.…”
Section: Discussionmentioning
confidence: 99%
“…Only three or four studies reported detailed data, therefore we could not draw exact conclusions for these two parameters due to the insufficient data. Previous two systematic reviews failed to show a significant effect in FEV 1 , likely due to small number of trials analyzed [38, 39]. Liu et al [39] converted and pooled continuous variable data such as blood and sputum eosinophils.…”
Section: Discussionmentioning
confidence: 99%